The Challenges Teachers in Interprofessional Teaching Face When Developing a Shared Assumption of Responsibility: A Mixed-Methods Study - Andrea Schlicker; Jan P. Ehlers (International Medical Education)
Background: Interprofessional education in the healthcare sector is becoming increasingly recognized in Germany; it is increasingly being included in the curriculum. The learners are usually the focus of the research. This study focusses on the teachers, as they are the ones who carry out the teaching and thus prepare the learners for practice. The aim of this study is to find out what skills interprofessional teachers should have for joint teaching and how the joint assumption of responsibility can be achieved in an interprofessional setting. Methods: Using a mixed-methods design, interprofessional courses were first identified across Germany in relation to the three professions of medicine, nursing and physiotherapy. Based on 76 fully completed quantitative questionnaires, the respondents’ views were surveyed with regard to the competences of the teachers, among other things. In 15 interviews based on these results, experts were asked more in-depth questions about competence limits and the assumption of responsibility, and the resulting data material was analyzed using Kuckartz’s structuring qualitative content analysis. Results: The quantitative results show that 70% of respondents (n = 53) consider it important to recognize profession-specific boundaries, while only 46% (n = 35) consider it important to assume joint responsibility. The qualitative part of the study shows that a basic understanding of the other professions is seen as conducive to dialog and collaboration. Furthermore, a shared assumption of responsibility is seen as an essential component of interprofessional teaching. Conclusions: In order to develop a shared assumption of responsibility, (self-)reflection is required; this also requires a conscious negotiation and development process on the part of the teachers. Teachers must align their joint actions with the needs of the learners so that they can later think and act across professions in patient care. As the process of (self-)reflection rarely takes place in mono-professional training programmes, opportunities to learn it are needed.